Arthroscopic Reinsertion of Acute Injuries of the Scapholunate Ligament Technique and Results - Carratalá, Vicente; Lucas, Francisco Javier; Miranda, Ignacio; Prada, Alfonso; Guisasola, Eva; Miranda, Francisco J. (Journal of Wrist Surgery, 2020)
Objective To describe a technique for treating acute injuries of the scapholunate ligament (SLL) by performing an arthroscopic reinsertion of the SLL and dorsal capsulodesis and to present the results obtained.Methods The study deals with an analytical, prospective clinical study that included 19 consecutive patients with acute injury of the SLL. The range of joint motion, grip strength, pain according to the visual analog scale, functional outcomes according to the Mayo Wrist Score (MWS), and the QuickDASH Score were studied preoperatively and 6 and 12 months postoperatively. The complications and necessary reinterventions were recorded.Results Nineteen patients with acute injury of the SLL were studied; mean age was 44 ± 2 years, 74% males, 58% complete rupture, and 42% partial rupture, treated with the above-mentioned technique. Thirty-seven percent also had a distal radius fracture and there was one case of perilunate dislocation. Improvement in pain, grip strength, joint balance, and functionality was observed 6 and 12 months postoperatively, with 79% of the cases with good or excellent resultsConclusion The arthroscopic reinsertion and dorsal capsular reinforcement of the SLL, allow a reliable and stable primary repair of the dorsal aspect of the ligament in acute or subacute SL injuries where there is tissue that can potentially be repaired, thus achieving an anatomical repair similar to that obtained with open surgery, but without the complications and stiffness secondary to aggressive interventions on the soft tissues that are inherent to the open dorsal approach.
Keywords: acute injury of the scapholunate ligament; scapholunate ligament complex; arthroscopy; dorsal capsular reinforcement